EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) DAN TEAMS GAMES TOURNAMENT (TGT) PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN DITINJAU DARI GAYA BELAJAR SISWA KELAS X SMK SE-KABUPATEN NGAWI TAHUN PELAJARAN 2015/2016 - Nirawati, Lia Septy; Kusmayadi, Tri Atmojo; Sujadi, Imam (Universitas Sebelas Maret, 2017)
Abstract: The purpose of this study was to know the effect of the learning models on the learning achievement in mathematics viewed from the students adversity quotient. The learning models compared were the cooperative learning of TAI, TGT, and direct learning model. The type of research was a quasi-experimental research with a 3x3 factorial design. The study population was all grade 10 students of Secondary Schools in Ngawi Regency in the academic year of 2015/2016. Instruments used for data collection were mathematics achievement test and learning style questionnaire. The data analysis technique used was the two-way ANOVA with unequal cell. Based on the hypothesis test, it was concluded that: 1) The mathematics learning achievement of the students who were treated by TAI learning model was better than the mathematics learning achievement of the students who were treated by TGT and direct learning model on equality and inequality, the mathematics learning achievement of the students who were treated by TGT learning model was better than the mathematics learning achievement of the students who were treated by direct learning model on equality an inequality; 2) The mathematics learning achievement of the students with visual type was better than the mathematics learning achievement of the students with auditory or kinesthetic type and the learning achievement of auditory type students was better than the learning achievement of kinesthetic type students on equality and inequality; 3) The visual type students who were treated by TAI learning model had better mathematics learning achievement than the students with TGT or direct learning model and the students mathematics learning learning achievement with TGT learning model was same the students with direct learning model; the mathematics achievement of auditory type students who were treated by TAI learning model had better mathematics learning achievement than the students with TGT or direct learning model and students who were treated by TGT learning model had better mathematics learning achievement than the students with direct learning model; the mathematics achievement of kinesthetic type students who were treated by TAI, TGT, and direct learning models had the same mathematics learning achievement; 4) In TAI, TGT and direct learning model, the mathematics learning achievement of visual type, auditory, and kinesthetic had the same mathematics learning achievement.Keywords: TAI, TGT, Direct Learning Model, Learning Style, Mathematics Learning Achievement